TRAINING AND MENTORING ON PACKAGING OPTIMIZATION OF POLINEMA CRISPY DUWET BANANA GEDEBOG CHIPS IN THE COMMUNITY OF DUWET VILLAGE, TUMPANG SUB-DISTRICT, MALANG DISTRICT - Baroroh Lestari; Eny Widiyowati; Achmad Suyono; Becik Gati Anjari; Diana Eka Poernamawati; Cahyo Ramadhan Pratama (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
This PKM/Service program aims to improve the packaging and promotion of "Debog Banana Duwet Polinema Crispy Chips" in Duwet Village, Tumpang District, Malang Regency. The residents of Duwet Village face challenges in effectively packaging and promoting their product, which currently lacks adequate branding and labels. To address these issues, this community service initiative aims to provide guidance and support in improving the packaging of the chips, as well as enhancing their promotional activities. Simple packaging equipment will also be provided to streamline the packaging process. The program's implementation will begin with partner coordination and conclude with a comprehensive evaluation. The outcomes of the training and mentoring activities reveal several key findings: Partners have limited knowledge about product quality improvement, affecting the product's market recognition. Current packaging methods used by partners are basic, consisting of plastic clips without product labels, limiting their market reach to the local community. "Kribog's DuPo Crispy" products, created by partners, lack attractive branding and labels. To ensure the sustainability of "Kribog's DuPo Crispy" products produced by our partners, the following recommendations are made: Conduct training sessions focused on enhancing product quality, fostering creativity, and innovation among "Kribog's DuPo Crispy" producers. Provide support in marketing strategies to address partners' limited knowledge in this area. Offer assistance in obtaining government-issued certifications, such as P-IRT licenses and food safety certifications, to ensure product quality and safety standards for "Kribog's DuPo Crispy."